Ecological approaches to perceptual learning: learning to perceive and perceiving as learning. (December 2019) - Szokolszky, Agnes; Read, Catherine; Palatinus, Zsolt; Palatinus, Kinga
In this theoretical review article, our primary goal is to contribute to the post-cognitivist understanding of learning to perceive and perceiving as learning, by discussing a framework for perception and perceptual learning initiated by James J Gibson, and extended by Eleanor J Gibson and others. This Ecological Psychology has a coherent set of assumptions based on the concept of mutualism between the perceiving organism and its surroundings, and the idea of affordances as action possibilities of the surround that are perceptible by the organism. At the same time, Ecological Psychology, broadly construed, consists of different perspectives that take different routes to address questions related to the core concepts of perceptual learning. In this article, we focus on three theoretical stances within Ecological Psychology on the issue of perceptual learning: that of Eleanor J Gibson, the current theory of direct learning by Jacobs and Michaels, and the "organicist" approach based on ideas of organicist biology and developments in evolutionary biology. We consider perceptual learning as embedded in development and evolution, and we explore perceptual learning in more depth in the context of tool use and language development. We also discuss the relation between Ecological Psychology and Enactivism on the nature of perception. In conclusion, we summarize the benefits of Ecological Psychology, as a robust but still developing post-cognitivist framework, for the study of perceptual learning and cognitive science in general.